S (Bachmanns) Anna.: Die Rolle der Herkunftsfamilie in Referenz und Namengebung in dörflichen Kommunikationsgemeinschaften - Schweden, Theresa (Linguistik Online, 2021)
In rural speech communities, when speakers refer to persons, their family of origin is omnipresent, not only by passing on the name of the family patriarch, but also in the serialization of surname and first name and in the grammatical structures of reference forms (der Müller Peter, s Müllers Peter). This paper portrays the diachronic development of reference forms and elaborates on their preservation in synchronic reference systems. Furthermore, it explores a referent’s linguistic categorization into social groups and shows that different grammatical structures foreground certain distinctions, which can also overlap. In rural villages, inofficial house names, derived from the patriarch’s first name or profession, are still in use. When an individual marries into another house, the reference to this person can change accordingly.